Using Nonpecuniary Strategies to Influence Behavior: Evidence from a Large-Scale Field Experiment - Ferraro, Paul J.; Price, Michael K. (The Review of Economics and Statistics, 2013)
The authors thank Kathy Nguyen for her support in conducting this experiment and for her assistance in creating the treatment messages and ensuring the experimental design was policy relevant. The authors also thank Herb Richardson for transferring the outcome data, Merlin Hanauer and Juan Jose Miranda for work to compile the data. John List, Subrendu Pattanayak, Laura Taylor, and participants at the 2009 AEA-ASSA meetings and seminars at the Georgia Water Wise Council, the Georgia Association